On Some Spaces Admitting Motion Groups of Maximum Order - Yegorov, A.; Yegorova, L. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Егоров, Л. Егорова. О некоторых пространствах, допускающих группы движений максимального порядка A. Jegorovas, L. Jegorova. Kai kurių erdvių, turinčių maksimalios eilės judesių grupes, klausimu